Empirical observation of natural farming inputs on nitrogen uptake, soil health, and crop yield of rice-wheat cropping system in the organically managed Inceptisol of Trans Gangetic plain - Darjee, Sibananda; Singh, Renu; Dhar, Shiva; Pandey, Renu; Dwivedi, Neeta; Sahu, Pramod Kumar; Rai, Mayank Kumar; Alekhya, Gunturi; Padhan, Smruti Ranjan; Ramalingappa, Pooja Laksmidevarhalli; Shrivastava, Manoj (Frontiers in Sustainable Food Systems, 2024)
Natural Farming represents an agro-ecological methodology for farming that emphasizes regenerative practices with an aim to promote holistic ecological balance and reduce the dependence on external inputs as well as financial resources. Substantial concern has recently arisen over the need to promote agroecosystems that are more sustainable in order to improve the deteriorating soil health as well as reversing the yield plateau of crop. So, the current on farm field experiment was executed comprising of 8 treatments with different combination of natural farming inputs (Ghanjeevamrit, Jeevamrit, Beejamrit), organic fertilizer (such as FYM), integrated nutrient management (NPK, FYM, Azotobacter and Azolla) and in-organic(NPK) to examine and compare the consequence of natural farming inputs, organic fertilizer and in-organic dosage of fertilizer on soil nitrogen uptake, soil physicochemical properties, soil biological properties, soil microbial population and crop yields in a rice-wheat cropping system over two crop seasons 2021–23 [rice (Pusa-1509) and wheat (HD-3086)]. The study results demonstrated that there was significant (p < 0.05) increase in the soil’s nitrogen availability and nitrogen uptake with the use of natural farming inputs as compared to control treatment, whereas, natural farming treatments (TNF1, TNF2, TNF3, TMNF) were inferior than integrated nutrient management (TINM) and recommended doses of fertilizer (TRDF) treatment in case of nitrogen uptake by both rice and wheat crop. The soil enzymatic activity (Dehydrogenase, β-glucosidase, and urease), soil microbial biomass carbon and nitrogen, and soil microbial population (Bacteria, fungi, and actinomycetes) were significantly (p < 0.05) higher in treatment receiving natural farming inputs compare to in-organic fertilizer and organic fertilizer. A positive and significant correlation was observed between potential mineralization nitrogen and soil enzymatic activity (Dehydrogenase, β-glucosidase, and urease), soil microbial biomass carbon and nitrogen and soil microbial population (Bacteria, fungi, and actinomycetes). The crop yield at the end of experiment recorded to be highest in treatment TINM (75% RDF (In-organic) + 25% RDF (FYM) + BGA) i.e., (Rice- 4.76 t/ha and Wheat- 5.82 t/ha) compared to TRDF and TNF. A crop yield reduction of 14.2% was observed in treatment receiving natural farming inputs compare to TINM. A significant increase in crop yield was observed in TMNF (Jeevamrit (25%) + Ghanjeevamrit (25%) + 50% RDF through FYM + Beejamrit) compare to Tc (Control) and TFYM (Farmyard manure). Therefore, our study suggests that adoption of natural farming inputs over time can facilitate the enhancement of soil biological health of Inceptisol of Trans Gangetic Plain of India.